The Role of the Vegfa C936t Polymorphism in the Development of Chronic Venous Insufficiency of the Legs And Its Analysis - Vasilevskiy Eduard Aleksandrovich (Zien Journals, 2023)
In 98 patients, an analysis of the genetic risk factor for the development of chronic venous insufficiency was carried out by studying the frequency of distribution of alleles and genotypes of the C936T polymorphism in the VEGFA gene. In both groups, the actual distribution of C807T polymorphism genotypes corresponded to those expected under the Hardy-Weinberg equilibrium (p <0.05). A significant relationship was established between the risk of developing chronic venous insufficiency and the distribution of predisposing/protective variants of the C807T polymorphism genotypes in the VEGFA gene. These data allow us to suggest testing this locus to predict the risk of occurrence and progression of chronic venous insufficiency>
Keywords: chronic venous insufficiency; vascular endothelial growth factor; genetic polymorphism